2022
DOI: 10.3390/ejihpe12110110
|View full text |Cite
|
Sign up to set email alerts
|

Admission Grades as Predictors of Medical Students’ Academic Performance: A Cross-Sectional Study from Saudi Arabia

Abstract: Background: Admission to medical school is competitive, and different countries use various tests in addition to high school grades to minimize selection bias. A few studies have been conducted to evaluate the usefulness of these tests as predictors for students’ academic performance. In this article, we aimed to assess factors that influenced students’ grades in medical school. Methods: A cross-sectional study included all students who graduated from the Faculty of Medicine at Jazan University between 2018 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Our result is supported by a study conducted in 2002 at Ain Shams University by Baker et al and the study showed that the most impactful lifestyle factors responsible for obesity are food consumption during stressful times and snacking between meals [16]. Thus, universities are required to provide students on on-campus activities that may reduce stress and more courses are required to train students on time management and to cope with stress [17,18].…”
Section: Discussionsupporting
confidence: 76%
“…Our result is supported by a study conducted in 2002 at Ain Shams University by Baker et al and the study showed that the most impactful lifestyle factors responsible for obesity are food consumption during stressful times and snacking between meals [16]. Thus, universities are required to provide students on on-campus activities that may reduce stress and more courses are required to train students on time management and to cope with stress [17,18].…”
Section: Discussionsupporting
confidence: 76%
“…Regarding to the relationship between the UEE score and academic achievement, the result of regression analysis showed that the UEE score was significantly and positively associated with pre-clinical and 5th year cumulative GPA, in line with others studies. 8,[36][37][38] Generally, the present study shows that the UEE score is a significant and positive predictor of medical students' university academic achievement, however, the amount of academic performance explained is quite low, with 32.7% and 24.4% in the pre-clinical and 5th year cumulative GPA, respectively. These variations are less than 40% leaving a large amount of variance still unexplained.…”
Section: Discussionmentioning
confidence: 44%
“…Research findings show that high school grade point average, UEE score, or standardized test score are assumed to be the best predictors of students' academic performance in higher education. [8][9][10] Several research reports in the literature, on the other hand, indicate that prior academic achievement is not the only determining factor of success in medical education and professional practice. [11][12][13] Studies have shown that, prior academic achievement accounts for only a portion of the variance in medical school performance and does not provide enough variance to allow meaningful differentiation on which to base selection decisions.…”
Section: Introductionmentioning
confidence: 99%